PEMBELAJARAN BAHASA DAN SASTRA BERBASIS KEARIFAN LOKAL SEBAGAI UPAYA OPTIMALISASI PENDIDIKAN KARAKTER MENUJU DUNIA GLOBAL - Leviana Disi; Dwi Yuli Hartati (Jurnal Pembahsi (Pembelajaran Bahasa Dan Sastra Indonesia), 2018)
Local wisdom in language learning and character reinforcement. In today's era of advanced communication intelligence is needed to utilize and package the values of local wisdom in a global context. In addition, no less important is the presence of creativity to bring back self-confidence in local behavior in national and global communications. Of course, the interpretation and creativity of literary authors become the basic necessity for maintaining local wisdom. Local color that is and carry the regionalism that is contained in cross-cultural communication of course reflects keiindonesiaan and through literature also we can put the values of local wisdom so thick that can be poured in the form of novels, short stories and poetry. Through language learning can be a tool to maintain the identity or identity of the nation because in the Indonesian language contained image of Indonesia. The image can be constructed and constructed by the author through character, characterizations, background and place specificities, as well as the story situation in the language. The characteristics, nuances, and breaths of Indonesianness can be exchanged in the language. Because language and literature have the ability to concoct the values of locality that make the reader has wisdom and gave birth to a positive attitude in interpreting the value of local wisdom which is the identity of the nation. Keywords— Language style satire of irony, cynicism and sarcasm